THE EFFECTIVENESS OF ISLAMIC EDUCATION LEARNING THROUGH INTERACTIVE APPROACHES FOR GENERATION Z STUDENTS - Fuadani, M. Mulya Zamzam Prasasti; Chotib, Moch.; Muhith, Abd.; Tamami, Badrut (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
Generation Z has unique characteristics that distinguish them from previous generations, such as dependence on technology and preference for dynamic and interactive learning methods. This article aims to examine the effectiveness of interactive approaches in learning Islamic Religious Education (PAI) for Generation Z students. This research uses a qualitative method with a case study approach in several secondary schools in Indonesia. Data were obtained through interviews, observations, and document analysis. The results show that interactive approaches, such as the use of digital media, group discussions, and simulations, can increase students' engagement, understanding, and application of religious values. This article recommends wider implementation of these methods to optimize PAI learning.